The Jains - Dundas, Paul 1952-2023 (London New York Routledge, 1992)
The question of Jain identity. Western views of the Jains -- 1. The fordmakers. The Vedic background. Going forth: the institution of world renunciation. The 'Sayings of the Seers'. The fordmakers and the ford. The sources for Mahavira's biography. Mahavira's date. Epithets. The transfer of the embryo. Mahavira's asceticism. Mahavira's relationship with Makkhali Gosala. Mahavira's relationship with Parshva. Mahavira's enlightenment. The preaching assembly. Mahavira as Great Man. The conversion of the ganadharas. The expansion of the fordmaker lineage. Early teachings -- 2. The Digambaras and the Shvetambaras. Sectarian origins. Sectarian attitudes. Social interaction. Can women attain deliverance? -- 3. Scriptures. Scripture as sacred object: the manuscripts at Mudbidri. Scripture as spectacle: the recitation of the Kalpasutra. Lost scriptures: the Purvas. Ardhamagadhi as scriptural language. Shvetambara traditions about scriptural transmission. The forty-five text Shvetambara canon. Enumeration of the Shvetambara scriptures. Digambara scriptures. The Five Homages. Jain libraries -- 4. Doctrine. Omniscience. The loka. The fundamental entities. Karma. The types of karma. Rebirth. Deliverance. Plants and animals. Kundakunda and the Digambara mystical tradition. God -- 5. History: from early times to the late medieval period. Mathura. Jainism in south India. Jain literature in Tamil. Jain kingship in Karnataka. Early Digambara sects. The bhattaraka. Mixed fortunes in the south. Shvetambara teachers. The temple-dwelling monks. The emergence of Shvetambara gacchas. The Kharatara Gaccha. The Tapa Gaccha. Relations with the Moslems. Shvetambara caste conversion -- 6. The ascetic. The stages of quality. Monks and nuns. Reasons for renunciation. Initiation. The Great Vows. The nature of non-violence. Asceticism. Meditation. Ascetic ritual: the Obligatory Actions. Interaction with the laity. Giving. Vegetarianism. Rules about Shvetambara ascetic behaviour. Sallekhana: the religious death. The role of the acarya -- 7. The lay person. The social milieu. What should a layman do? Banarsidas. Wealth, honour and piety. Bidding. Fasting. Worship. Background. Puja. The puja of eight substances. The purpose of puja. Goddesses. Yearly festivals. Pilgrimage and holy places. Historical background. Mount Shatrunjaya. Shravana Belgola -- 8. Jain relativism and relations with Hinduism and. Buddhism. The doctrine of manypointedness. The Jains and the Hindus. The Jains and the Buddhists -- 9. Recent developments. Lonka. The Sthanakvasis. Acarya Bhikshu and the Terapanth. Shrimad Rajacandra. The Kanji Svami Panth. The Jain diaspora. The future
The question of Jain identity. Western views of the Jains -- 1. The fordmakers. The Vedic background. Going forth: the institution of world renunciation. The 'Sayings of the Seers'. The fordmakers and the ford. The sources for Mahavira's biography. Mahavira's date. Epithets. The transfer of the embryo. Mahavira's asceticism. Mahavira's relationship with Makkhali Gosala. Mahavira's relationship with Parshva. Mahavira's enlightenment. The preaching assembly. Mahavira as Great Man. The conversion of the ganadharas. The expansion of the fordmaker lineage. Early teachings -- 2. The Digambaras and the Shvetambaras. Sectarian origins. Sectarian attitudes. Social interaction. Can women attain deliverance? -- 3. Scriptures. Scripture as sacred object: the manuscripts at Mudbidri. Scripture as spectacle: the recitation of the Kalpasutra. Lost scriptures: the Purvas. Ardhamagadhi as scriptural language. Shvetambara traditions about scriptural transmission. The forty-five text Shvetambara canon. Enumeration of the Shvetambara scriptures. Digambara scriptures. The Five Homages. Jain libraries -- 4. Doctrine. Omniscience. The loka. The fundamental entities. Karma. The types of karma. Rebirth. Deliverance. Plants and animals. Kundakunda and the Digambara mystical tradition. God -- 5. History: from early times to the late medieval period. Mathura. Jainism in south India. Jain literature in Tamil. Jain kingship in Karnataka. Early Digambara sects. The bhattaraka. Mixed fortunes in the south. Shvetambara teachers. The temple-dwelling monks. The emergence of Shvetambara gacchas. The Kharatara Gaccha. The Tapa Gaccha. Relations with the Moslems. Shvetambara caste conversion -- 6. The ascetic. The stages of quality. Monks and nuns. Reasons for renunciation. Initiation. The Great Vows. The nature of non-violence. Asceticism. Meditation. Ascetic ritual: the Obligatory Actions. Interaction with the laity. Giving. Vegetarianism. Rules about Shvetambara ascetic behaviour. Sallekhana: the religious death. The role of the acarya -- 7. The lay person. The social milieu. What should a layman do? Banarsidas. Wealth, honour and piety. Bidding. Fasting. Worship. Background. Puja. The puja of eight substances. The purpose of puja. Goddesses. Yearly festivals. Pilgrimage and holy places. Historical background. Mount Shatrunjaya. Shravana Belgola -- 8. Jain relativism and relations with Hinduism and. Buddhism. The doctrine of manypointedness. The Jains and the Hindus. The Jains and the Buddhists -- 9. Recent developments. Lonka. The Sthanakvasis. Acarya Bhikshu and the Terapanth. Shrimad Rajacandra. The Kanji Svami Panth. The Jain diaspora. The future.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Jainism; Jains; Religion